Wortschatz: Theorie, Empirie, Dokumentation - Engelberg, Stefan; Kämper, Heidrun; Storjohann, Petra (Germanistische Sprachwissenschaft um 2020, 2018)
Our traditional understanding of the lexicon has been changed by recent attention to the demarcation between grammar and the lexicon, increased attention to the phenomena of variance, the observation of quantitative divisions between lexical phenomena in large text corpora, and the development of Internet lexicographic formats. The volume explores the phenomena shaping these changes in order to describe current lexicological theory and practice.